2021
DOI: 10.1155/2021/8493464
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Innovation and Development of University Education Management Informationization in the Environment of Wireless Communication and Big Data

Abstract: The development of information technology has spawned a new type of demand and management analysis model of big data. The value of data is vividly reflected in the contemporary era, and all walks of life have devoted great energy to the construction and use of informatization. The object of college education and management is the group of college students who are most closely connected with contemporary trends. Their thoughts are active, their state is changeable, and they are very sensitive to external stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Based on these details, the Luban will complete the design process, which includes material analysis, drawing, and typesetting, for them. During the 2019 shopping carnival, Luban generated a total of 1 billion posters at a rate of 8,000 posters per second, which were used by merchants to promote their products and increase their sales [15,16]. e Alibaba intelligent design work platform, which makes use of artificial intelligence technologies, is changing the design technique used by traditional designers in the industry.…”
mentioning
confidence: 99%
“…Based on these details, the Luban will complete the design process, which includes material analysis, drawing, and typesetting, for them. During the 2019 shopping carnival, Luban generated a total of 1 billion posters at a rate of 8,000 posters per second, which were used by merchants to promote their products and increase their sales [15,16]. e Alibaba intelligent design work platform, which makes use of artificial intelligence technologies, is changing the design technique used by traditional designers in the industry.…”
mentioning
confidence: 99%
“…Li, W., et al discussed the role of information technology in the educational management of universities and considered that information technology is an inevitable choice for the educational management of universities. Klein, L. L., et al analyzed the effectiveness of lean management practices in promoting sustainable development of higher education management, using academic staff of higher education colleges in Brazil and Portugal as examples of their studies [14]. The results showed that lean management practices effectively improved decision-makers' leadership in higher education institutions and led to the higher motivation of academic researchers [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the deployment and use of technologies for data collection and analysis can pose challenges (West et al, 2020). This includes ensuring that the technologies are compatible with existing systems and processes, as well as adequately trained staff to utilize these technologies effectively (Li, 2021). Overall, the challenges in using university data for decision-making arise from technical limitations in infrastructure and monitoring capabilities, as well as organizational obstacles such as the lack of a comprehensive platform and difficulties in deploying and using technologies (Munshi & Alhindi, 2021).…”
Section: Decision-making Using University Datamentioning
confidence: 99%
“…It is crucial to collect data and develop and utilise it effectively (Falola et al, 2018). By utilising big data collection and analysis, universities can promote the construction of educational management information systems that make better use of information equipment (Li, 2021). This, in turn, can improve the overall level of college education management.…”
Section: Challenges With University Datamentioning
confidence: 99%